Reconstructing Employee Loyalty in the Era of Silent Resignation at Remote-Based Workplaces - I Dewa Ketut Raka Ardiana; Muhamad Ahsan; Olivia Winda Ony Panjaitan; Jefri Putri Nugraha (Jurnal Ilmiah Manajemen Kesatuan, 2026)
This study aims to reconstruct the concept of employee loyalty in remote work settings by examining the dynamics of silent resignation, where employees withdraw emotional and psychological engagement without formally resigning. A phenomenological qualitative study was conducted through semi-structured interviews with 25 remote employees and HR practitioners in Indonesia, analyzed using open, axial, and selective coding to explore emerging dimensions of employee loyalty in a post-pandemic digital work context. The findings reveal a shift in the meaning of loyalty from contractual to relational, characterized by dimensions such as organizational trust, work flexibility, meaningful work, and the alignment between personal and organizational values. Traditional control-based HR management strategies are increasingly ineffective and must be replaced with approaches centered on trust, transparency, and autonomy. The study concludes that employee loyalty in the remote work era can no longer be assessed using conventional indicators such as tenure or structural compliance; instead, it is shaped by interpersonal relationship quality, digital work experiences, and the intrinsic value provided by the organization. This research contributes to expanding the conceptual understanding of employee loyalty in digitally decentralized organizations and provides a foundation for developing more adaptive HRM strategies for employee engagement and retention in the post-normal era.